Qur'anic memorization : exploring the cognitive processes among the huffaz - Zarina binti Mohamed @ Ayub (Institute of Education, International Islamic University Malaysia, 2014)
Through a framework of cognitive psychology, this study explores the cognitive processes involved in memorising the Qur'an using the Information Processing Approach (IPA). This study adopts a qualitative case study design consisting of in-depth interviews with five (5) experienced huffaz (memorisers of the Qur'an). The responses revealed that sensory memory, Short-Term Memory (STM) and Long-Term Memory (LTM) processes are involved in memorising the Qur'an. During the sensory memory stage, participants highlighted the importance of teacher-student face-to-face encounter to ensure students achieved proficient Qur'anic recitation based on a recognized sanad (recitation style) before they start to memorise. This significant process is termed as talaqqi-musyafahah (face-to-face verbal instruction). Due to the fact that the Qur'an is Kalamullah (Speech of Allah), all participants pointed out that careful attention to details is critical. Participants emphasized the need to observe high levels of attention when transferring the information from sensory memory to STM. Data analysis revealed that at least ten (10) encoding strategies are used in the Qur'anic memorisation process which include: takrir (articulatory rehearsal process); muraja'ah (accumulative revision); chunking; complex sentences; writing and note taking; gradual testing strategy; visual imagery; pondering upon the meaning of the ayah; tazkirah; and self-reference effect. With regards to permanent retention of the Qur'an in the heart of the huffaz, the participants pointed out at least four (4) retention strategies are applied which include: Istiqamah(consistent in daily muraja'ah (revision)); Istiqamah in 'amal (reflecting the Qur'an through behaviour – portraying the Akhlaq (moral character) of the Qur'an); teaching the Qur'an to others; and serving as an Imam (leader for congregational prayer).The participants emphasised that one's faith is the most significant factor for ensuring commitment to Qur'anic memorisation. This study attempted to initiate further investigation on this faith oriented memorisation tradition from a cognitive psychological perspective. This research is exploratory and there is a need for additional studies to establish the theoretical foundation of Qur'anic memorisation, particularly in the field of cognitive psychology.